Interimplant Papilla Reconstruction by Using Demineralized Freeze Dried Bone Allograft Block Fixed by Titanium Screw: A Case Report - Preeti Charde; M. L. Bhongade; Aniruddha Deshpande; Anendd Jadhav; Kaustubh Thakare; Priyanka Jaiswal (Hindawi Limited, 2012)
Dental implants are now considered as a predictable treatment modality for the oral rehabilitation of partially or fully edentulous patients. Recently emphasis has changed towards achieving a predictable esthetic success. Creating aesthetically successful implant-supported restoration in the anterior region of oral cavity depends on the presence of interimplant papilla when multiple implants are used. The present paper reports a case of interimplant papilla reconstruction in esthetic zone of maxilla during one stage early loading multiple implant procedure using demineralized freeze dried bone allograft block fixed by titanium screw.